Antiproliferative Effect of Rottlerin on Sk-Mel-28 Melanoma Cells. (28th May 2015) - Daveri, Elena; Valacchi, Giuseppe; Romagnoli, Roberta; Maellaro, Emilia; Maioli, Emanuela
Abstract : Melanoma is the most aggressive and chemoresistant form of skin cancer. Mutated, constitutively active B-RAF is believed to play a crucial role, although the selective B-RAF inhibition has shown poor clinical success, since phenomena of resistance usually occur, likely arising from additional genetic aberrations, such as loss of function of p53 and PTEN, overexpression of cyclin D1, hyperactivation of NF- κ B, and downregulation of p21/Cip1. Since all of them are present in the Sk-Mel-28 melanoma cells, this cell line could be an ideal, albeit hard to study, model to develop new therapeutic strategies. In the current study, we tested the cytostatic action of Rottlerin on Sk-Mel-28 melanoma cells, on the basis of the known Rottlerin effects on the main proliferative signaling pathways. We presented evidence that the drug inhibits cell growth by an Akt- and p21/Cip1-independent mechanism, involving the dual inhibition of ERK and NF- κ B and downregulation of cyclin D1. In addition, we found that Rottlerin increases ERK phosphorylation, but, surprisingly, this resulted in decreased ERK activity. Pull-down experiments, using Rottlerin-CNBr-conjugated Sepharose beads, revealed that Rottlerin binds to ERK, independently from its phosphorylation status. This direct interaction could in part explain the paradoxical blockage of ERK downstream signaling and growth arrest.